Assessment of job stress among non-teaching staff: A cross-sectional study at teaching hospital, Central India - Manish Arun Dhakate; Vijay Kishanrao Domple; Umesh Shankarrao Joge; Gautam Marotrao Khakse; Prabhakar Atmaram Hiwarkar (Occupational Health and Safety Society of Nepal, 2022)
Introduction: Job stress plays an important role in the maintenance of organizational performance. A key aspect of job stress is increased workload, role conflict, poor job control, lack of support from coworkers and interpersonal conflict. Most studies in the field of job stress have focused on private sectors. The objective of this study was to assess the job stress among non-teaching staff at government teaching hospital. Methods: The present cross-sectional study was carried out in a government teaching hospital in central India between Jan 2020 to March 2020 among 90 participants purposively chosen for the study. New Job Stress Scale was used to assess the extent of stress among the participants. Approval from Institutional Ethical Committee was obtained before commencing the study. Data was analyzed by SPSS version 20 for percentages, mean and standard deviation. Results: A moderate level of stress affects 47.78 percent of participants. The present study found that most problematic dimensions of job stress variables were dimension of role conflict with as many as 51% of participants had experience role expectation conflict. Conclusion: We can infer from this finding that we need to have formal job description written for their non-teaching staff so that their role should be clear and unambiguous.